Characterization of pandemic influenza A (H1N1) virus hemagglutinin specific polyclonal antibodies for biosensor applications. Issue 3 (23rd September 2013) - Athmaram, T.N.; Saraswat, Shweta; Sikarwar, Bhavna; Verma, Shailendra Kumar; Singh, Anil K.; Boopathi, M.
<x xml:space="preserve">Abstract</x> In this study, recombinant hemagglutinin protein (rH1N1HA) of Pandemic influenza virus and polyclonal antibodies against it for biosensor applications have been characterized. For rapid and high sensitive detection of H1N1 virus or its antibodies, PCR‐free and label free detection method based on a surface plasmon resonance technique has been proposed. The glycosylated H1N1HA protein was expressed in yeast and the authenticity of the expressed protein was confirmed by Western blotting. Rabbit polyclonal antibodies developed against rH1N1HA protein were evaluated for their ability to neutralize H1N1 virus through plaque reduction neutralization test and indirect ELISA. Affinity purified anti‐H1N1HA IgG were characterized further for their specificity, affinity of interaction, the association and dissociation rates at which they interact through surface plasmon resonance technique. The equilibrium constant and maximum binding capacity of analyte was found to be 49.7 nM and 47.28m°, respectively. The assay could detect a lowest IgG of 0.5 ng on a rH1N1HA coated chip. Combined with the high sensitivity of surface plasmon resonance technique and specificity of the reagents, it is possible to develop a rapid detection assay for monitoring influenza infections. J. Med. Virol. 86:363–371, 2014. © 2013 Wiley Periodicals, Inc.